Mexico : Report on Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report ;, 2010)
Mexican macroeconomic statistics are in a period of transition as recent laws have strengthened the legal backing and have changed institutional arrangements. Mexico is in observance of the Special Data Dissemination Standard, meeting the specifications for data coverage, periodicity and timeliness, and the dissemination of advance release calendars. Executive Directors suggest enhancing cross-domain cooperation within and among statistical agencies and national accounts, government finance, and monetary and balance of payments statistics with the purpose of improving their international comparability.